ANTIMICROBIAL EFFECTS OF OCIMUM SANCTUM ON ORAL MICROBES - Parida, Amrita; Siddeeqh, Salman; Jose, Maji; V., Manju (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Ocimum sanctum (Tulsi) of the Lamiaceae family has been used since centuries for its medicinal properties. Tulsi powder has been utilized for cleaning tooth and is known to be effective in maintaining oral hygiene. Although the medical usefulness of tulsi is investigated extensively, its effectiveness in treating oral diseases is not yet established, and only a few studies are available in the literature regarding this aspect. Therefore, in the current study, the antimicrobial activity of alcoholic extract of tulsi on oral microbes was explored. Methods: Ethanolic extract was obtained from the leaves of O. sanctum (tulsi) using the Soxhlet apparatus. The concentration of 400 μg/ml was chosen to test the antimicrobial properties against common oral microbes such as Prevotella intermedia, Streptococcus mutans, Candida albicans, Lactobacillus acidophilus, Streptococcus mitis, and Peptostreptococcus using agar well diffusion and broth dilution method. Chlorhexidine was a positive control. To compare and correlate the results, Mann–Whitney U-test was applied. Results: The ethanolic extract at a concentration of 400 μg/ml showed an inhibitory effect against Streptococcus and Streptococcus with an inhibitory zone of 7.33 mm each. The extract was found to be effective against P. intermedia and Peptostreptococcus. It was also effective against candida (zone of inhibition was 10.67 mm). However, no inhibitory effect was seen on Lactobacillus. Conclusion: O. sanctum extract was found to have inhibitory effects on oral microbes, and hence, pharmaceutical formulations prepared from tulsi extracts could have a potential to be used as a part of routine dental hygiene.